(3adSaI GadGWf heQGJH CLRGFgG ef ChdgG Edi BNQgGs
(3ChdgG (B:s
(3HYO GdHSedI aNU ChdGk ef ceGd GdGfSGf ef MjK gh GfSGf Gj TF ef GdGTjGA GdJj JhLO GdGfSGf hjUjQ eZHhWkG s
(3BNQgG (B:s
(3hhLg GdJOHjQ aj fbdge YfgG bdjdkG hhUa GdGQGA hGdfhGejS GdJj jfbdhg GdjgG HYO Cf Jfbd SjQge hfhGejSge s
(3Vef eLehY , JQJjHgG (B: 1s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs